Kontribusi Kecerdasan Moral dan Kecerdasan Interpersonal Terhadap Kedisiplinan Mematuhi Tata Tertib Sekolah - Muryastuti, Diah Wahyu; Sugiharto, DYP (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
Abstract This research was conducted based on phenomena that occur in grade X SMK N 7 Semarang that has breach of discipline. The purpose of this research is to find empirical evidence about the contribution of moral intelligence and interpersonal intelligence against discipline in complying with the code of conduct of the school. This research is ex-post facto research. This research was conducted at SMK N 7 Semarang grade X, with 176 student subjects. Data collection methods used the scale of psychology. Data analysis techniques using multiple regression analysis. The results showed that moral intelligence partially has positive correlation to the discipline in complying with the code of conduct of the school (rparsial = .357, p<.01) . Interpersonal intelligence partially has positive correlation (rparsial = .279, p<.01) . And next, moral intelligence and interpersonal intelligence together contribute to the discipline in complying with the code of conduct of the school of 55,3%. During the action, it shows the moral intelligence and interpersonal intelligence contribute to discipline in complying with the conduct of the school.